Short-term CBT of mixed anxiety-depressive disorder - Lahutina, Софія (Psychosomatic Medicine and General Practice, 2018)
Introduction. Epidemiological studies indicate that anxiety and depressive disorders are the most common mental health problems, without timely and effective help, they can have a pronounced negative impact on the quality of life of a person. Cognitive-behavioral therapy is one of the most researched and effective psychotherapeutic methods for treating depression, anxiety disorders, PTSD, eating disorders, and many others. Purpose. The purpose of this article is to show the effectiveness of short-term cognitive-behavioral psychotherapy of mixed anxiety and depressive disorder. The clinical case presented in this article illustrates a person whose mental disorder caused somatic symptoms, reduced life quality. Materials and methods. Patient K., 52 years old, went to the Clinic for comprehensive psychotherapy rehabilitation with complaints of anxiety, insomnia, limb tremor, weakness in the legs, feeling of tightness in the chest, lower abdominal pain, lack of appetite. She noted weight loss, dry mouth, digestive disorders. The patient was disturbed by unbearable anxiety-depressive thoughts, feeling of irritability, and low mood. Complex treatment of the patient - psychotherapeutic interventions in combination with pharmacotherapy was carried out. Cognitive behavioral therapy (CBT) has become the method of choice in this clinical case. Results. The introduction of cognitive-behavioral therapy in national protocols of treatment of mental disorders will improve the quality of life, facilitate faster re-socialization and rehabilitation of patients. This clinical case meets the criteria of psychosomatic disorder, because it combines anxiety, depressive symptoms, autonomic symptoms, psychogenic prerequisites for the disorder. This patient has a combination of mental and somatic symptoms, with the predominance of the latter. The combination of medication and psychotherapy methods (including cognitive-behavioral therapy) according to international protocol, produces positive results in a limited time, reduces anxiety, and significantly reduces depression. Such a combination is most appropriate, since the number of relapses after the use of complex therapy is objectively shother in comparison of the use of both methods separately, our clinical case confirms this.